The use of social media, e-mail and instant messaging as the predictors of an employee’s work performance / Ainaa Idayu Iskandar, Ahmad Fadhly Arham and Najiah Shohaime - Iskandar, Ainaa Idayu; Ahmad Fadhly, Arham; Shohaime, Najiah (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Computer mediated communication tools such as e-mail, instant messaging and social media has become common tools used to deliver messages to get prompt responses. It is an opportunity for organizations to use and fully utilise the functions of e-mail, instant messaging and social network to improve work performance. This study was conducted at one of the public service departments in Malaysia with 132 number of questionnaires distributed. The data was analysed using multiple regression. Findings showed that there is significant relationship between the use of instant messaging and social network with performance, whereas the results for the use of e-mail showed otherwise. This paper provides a better knowledge and information on how to increase the work performance of employees through the use of instant messaging and social network. The findings may also contribute to the existing literature.